The anti-caspase inhibitor Q-VD-OPH prevents AIDS disease progression in SIV-infected rhesus macaques - Laforge, Mireille (2018)
Apoptosis has been proposed as a key mechanism responsible for CD4+ T cell depletion and immune dysfunction during HIV infection. We demonstrated that Q-VD-OPH, a caspase inhibitor, inhibits spontaneous and activation-induced death of T cells from SIV-infected rhesus macaques (RMs). When administered during the acute phase of infection, Q-VD-OPH was associated with (a) reduced levels of T cell death, (b) preservation of CD4+/CD8+ T cell ratio in lymphoid organs and in the gut, (c) maintenance of memory CD4+ T cells, and (d) increased specific CD4+ T cell response associated with the expression of cytotoxic molecules. Although therapy was limited to the acute phase of infection, Q-VD-OPH-treated RMs showed lower levels of both viral load and cell-associated SIV DNA as compared with control SIV-infected RMs throughout the chronic phase of infection, and prevented the development of AIDS. Overall, our data demonstrate that Q-VD-OPH injection in SIV-infected RMs may represent an adjunctive therapeutic agent to control HIV infection and delaying disease progression to AIDS.